p53/Drp1-dependent mitochondrial fission mediates aldosterone-induced podocyte injury and mitochondrial dysfunction - Yuan, Yanggang; Zhang, Aiqing; Qi, Jia; Wang, Hui; Liu, Xi; Zhao, Min; Duan, Suyan; Huang, Zhimin; Zhang, Chengning; Wu, Lin; Zhang, Bo; Zhang, Aihua; et al. (American journal of physiology. Renal physiology, 2018)
Mitochondrial dysfunction is increasingly recognized as an important factor in glomerular diseases. Previous study has shown that mitochondrial fission contributed to mitochondrial dysfunction. However, the mechanism of mitochondrial fission on mitochondrial dysfunction in aldosterone-induced podocyte injury remains ambiguous. This study aimed to investigate the pathogenic effect of mitochondrial fission both in vivo and in vitro. In an animal model of aldosterone-induced nephropathy, inhibition of the mitochondrial fission protein dynamin-related protein 1 (Drp1) suppressed aldosterone-induced podocyte injury. In cultured podocytes, aldosterone dose dependently induced Drp1 expression. Knockdown of Drp1 inhibited aldosterone-induced mitochondrial fission, mitochondrial dysfunction, and podocyte apoptosis. Furthermore, aldosterone dose dependently induced p53 expression. Knockdown of p53 inhibited aldosterone-induced Drp1 expression, mitochondrial dysfunction, and podocyte apoptosis. These findings implicated that aldosterone induced mitochondrial dysfunction and podocyte injury mediated by p53/Drp1-dependent mitochondrial fission, which may provide opportunities for therapeutic intervention for podocyte injury.